(untitled) (International Journal of Nursing Education, 2019)
There are a variety of teaching strategies that instructors can use to improve student learning. It is of great importance to select appropriate teaching strategies in nurse education to make the training more appealing and more effective. In this article, few teaching strategies will be introduced to help instructors learn how to involve the teaching strategy in the nurse education, Faculty and students work together to create environments that promote leadership, Interprofessional education, transformative research and cultural inclusiveness. Through innovative teaching and learning approaches that address a variety of learning styles, professors actively engage students. Whether it’s future researchers and nursing faculty looking to advance their careers or nurses, nurse practitioners and physician assistants seeking greater clinical knowledge, all students at the School of Nursing benefit from professors with diverse interests who create learning environments that empower them to be agents of health care change. Technology allows students to maximize learning time by completing coursework before coming to class. The elimination of lecture-style instruction engages students in a twoway flow of information. Faculty recognizes adults learn differently and instruction must accommodate multiple learning styles. New research validates that student-driven education promotes retention far better than lecturing. Ultimately, School of Nursing graduates effectively function to the highest standards of care